Simultaneous Estimation of Glimepiride, Rosiglitazone and Pioglitazone Hydrochloride in the Pharmaceutical Dosage Form - Freddy H. Havaldar; Dharmendra L. Vairal (E-Journal of Chemistry)
A simple, specific, accurate and economical gradient reversed phase liquid chromatographic (RP-HPLC) method was developed and subsequently validated for the determination of glimipiride, rosiglitazone and pioglitazone hydrochloride. Separation was achieved with a nucleodur C–18 column having 250×4.6 mm i.d. with 5 µm particle size and water HPLC grade adjusted to pH 3.0 using diluted orthophosphoric acid and acetonitrile (80:20 v∕v) with gradient program as eluent at a constant flow rate of 0.8 ml per min. UV detection was performed at 215 nm. The retention time of glimipiride, rosiglitazone and pioglitazone hydrochloride were about 17.9 min, 6.31 min and 8.24 min respectively. This method is simple, rapid and selective and can be used for routine analysis of antidiabetic drugs in pharmaceutical preparation. The proposed method was validated and successfully used for estimation of glimipiride, rosiglitazone and pioglitazone hydrochloride in the pharmaceutical dosage form.